Glossário ilustrado da terminologia da marcenaria de Nova Timboteua - PA - SILVA, Lucidalva Marques da (2024)
This course completion work (TCC) consists of the elaboration of an Illustrated Glossary of Woodworking Terminology1 in the municipality of Nova Timboteua - PA. It is structured in a semi-systematic way: in alphabetical order and in three conceptual fields, and brings a survey of the vocabulary that characterizes the Woodworking Terminology (specialized lexicon) used by a group of 08 woodworkers (research informants) who work in handmade manufacture of domestic furniture and frames at the São Francisco workshop, located in the urban area of ​​the municipality. The work was developed based on the theoretical-methodological orientations of Lexicology, Socioterminology, Terminology and Terminography, with emphasis on research in Terminography, a science that corresponds to the application of linguistic studies developed by terminology to the technique of elaborating specialized dictionaries and glossaries. In this perspective, this work has as its main object of analysis and linguistic description the terminological unit - the term - specialized lexia present in the discourse of professionals who share the same area of ​​human knowledge. The terminological glossary presents the survey record of 98 terms (terms – entry and their lexical and morphosyntactic terminological variants), whose description and analysis starts from the social, situational and sociolinguistic contexts in which the terms circulate. Therefore, the aim of this work is to contribute to the documentation and preservation of the specialized lexicon in the area of ​​woodworking activity, contributing to the advancement of terminological studies and the social rescue of this still poorly documented craft.